2000
DOI: 10.1159/000014222
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Pentoxifylline as an Anti-Inflammatory Agent in Experimental <i>Escherichia coli</i> Meningitis in the Newborn Piglet

Abstract: This study was done to evaluate the anti-inflammatory effect and the ensuing neuroprotective effect of pentoxifylline in neonatal experimental bacterial meningitis. Newborn piglets were divided into three groups: 10 in the control group (CG), 13 in the meningitis group (MG), and 13 in the meningitis with pentoxifylline group (PG). Meningitis was induced by intracisternal injection of 108 colony-forming units of Escherichia coli in 100 μl of saline. In PG, 20 mg/kg of pentoxifylline was given as a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
3
0
1
Order By: Relevance
“…PTX increases cAMP levels in the cell by inhibiting the phosphodiesterase enzyme. This increase leads to ATP enhancement, which in turn results in cellular glycolysis, energy production, increased sperm motility, and increased ATP production ( Park et al, 2000 ), which can be satisfactory explanation for the results in the present study. The present results affirm that adding PTX to the extender could increase progressive motility before cryopreservation.…”
Section: Discussionsupporting
confidence: 85%
“…PTX increases cAMP levels in the cell by inhibiting the phosphodiesterase enzyme. This increase leads to ATP enhancement, which in turn results in cellular glycolysis, energy production, increased sperm motility, and increased ATP production ( Park et al, 2000 ), which can be satisfactory explanation for the results in the present study. The present results affirm that adding PTX to the extender could increase progressive motility before cryopreservation.…”
Section: Discussionsupporting
confidence: 85%
“…The brain of the newborn, in a phase of accelerated growth, contains high concentrations of polyunsaturated fatty acids, thus is particularly suscepti- ble to the lesion induced by O 2 free radicals. In addition, these factors coincide also with the fact that the lowest levels of oxygen free radical scavengers and antioxidant enzymes are occurring in the neonatal period 12 . Experimental studies have demonstrated the sequential emergence of the bioactivity of TNF-α, IL-1β and IL-6 in CSF after injection of PLS or viable meningococci in the subarachnoid space 13 .…”
Section: Discussionmentioning
confidence: 74%
“…Experimental studies have demonstrated the sequential emergence of the bioactivity of TNF-α, IL-1β and IL-6 in CSF after injection of PLS or viable meningococci in the subarachnoid space 13 . Probably the increase of the production of TNF-α at the beginning of the inflammatory reaction 12,14 induces the secretion of IL-1β, both cytokines being responsible for the first steps of the inflammation cascade that leads to the destruction of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of intracellular cAMP can be inhibitid by phosphodiesterase inhibitors, such as the type IV phosphodiesterase inhibitor rolipram. In addition, the phophodiesterase inhibitor pentoxifylline (a methylxanthine derivative) reduced inflammation in the subarachnoid space in several models of bacte- rial meningitis but had no significant effect on blood-brain barrier permeability or neuronal damage (106,133,175). New xanthine derivatives such as lisofylline, which have a similar mode of action, are less toxic, making their clinical use more feasible (165).…”
Section: Protect Against Injurymentioning
confidence: 99%